JAMINAN PRODUK HALAL SEBAGAI PERLINDUNGAN HAK WARGA NEGARA - Humiati; Silfiah, Rossa Ilma (Lex Journal: Kajian Hukum & Keadilan, 2021)
The state as a protector of the guarantee of the rights of citizens is the essence of the purpose of the establishment of a state. The guarantee of halal products for food and beverages is one form of such protection. This has been manifested in the formation of laws and regulations related to halal product guarantees in addition to Law Number 8 of 1999 concerning Consumer Protection which was promulgated earlier. Halal Product Guarantee is implemented in Halal Certification which aims to provide legal certainty and legal protection for consumers, especially Muslim consumers. Halal-certified Product Guarantee is regulated in Law Number 33 of 2014 concerning Halal Product Guarantee (JPH). The existence of this law is important in the midst of free trade that is currently happening. This policy is expected to stop the supply of food that is not clearly halal. This protection is very relevant to the purpose of the implementation of Islamic law, which is to protect religion, protect the soul, protect the mind, protect offspring and protect property. This study will examine five things that are protected in Islamic law. So it will appear that the implementation of the Halal Product Guarantee is very much needed for the sustainability of human life.Keywords: Halal Guarantee, Legal Protection